Implementation and feasibility of electronic patient-reported outcome (ePRO) data dntry in the PRAEGNANT real-time advanced and metastatic breast cancer registry = Evaluation einer elektronischen Erhebung von Patient-reported-Outcomes (PROs) im PRAEGNANT-Register - Wallwiener, Markus; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2017)
Purpose: Patient-reported outcomes (PROs) have been incorporated into clinical trials for many symptoms and medical conditions. A transition from paper-based capture of PROs to electronic PROs (ePROs) has recently started. This study reports on the feasibility of ePRO assessment in a prospective registry including molecular data for patients with advanced breast cancer. Methods: As part of the PRAEGNANT network, patients were invited by clinical trial staff, physicians, and nurses to complete three standardized Internet-based questionnaires (EQ 5D 5 L, CES-D and IPAQ). Feasibility was assessed by the staff members who assigned the user accounts by the patients. The completeness of the questionnaires was also assessed. Results: Fifteen of 17 patients who were asked agreed to participate to complete the PRO questionnaires (EQ-5D-5L and CES-D). However, the IPAQ (physical activity) questionnaire was only validly completed by 9 patients. Feasibility was ranked better by the physicians and dedicated clinical trial staff than by the nursing staff. Conclusions: Incorporating ePRO questionnaires into an advanced breast cancer registry is feasible, and no major hurdles were reported. Involving stakeholders from the start, the application is tailored to the capacities and abilities of both patients and clinical staff. The patientsʼ compliance was better with some questionnaires, but others may present difficulties
Publikationsdatum: 24. August 2017 (online)
Gesehen am 22.06.2018